Synthesis of calcium phosphate crystals with thin nacreous structure. Issue 6 (22nd January 2016) - Chen, Song; Grandfield, Kathryn; Yu, Shun; Engqvist, Håkan; Xia, Wei
Abstract : Calcium phospate crystals with a thin nacreous structure were synthesized and characterized. Abstract : Nacre-like structures have attracted great interest in recent years due to their outstanding toughness, stiffness and impact resistance. However, there is a challenge associated with engineering nacre-like calcium phosphate crystals. In this study, thin nacreous-like monetite sheets were synthesized in solutions guided by a surfactant. The influence of temperature, initial pH, Ca/P ratio, stirring time and the concentration of cetyltrimethylammonium bromide (CTAB) on the nacre-like structure has been studied. Findings showed that a nacre-like structure could only be formed at a high temperature (90 °C), high initial pH (11), sufficient stirring time (3 h), and under the presence of CTAB. A small-angle X-ray scattering experiment carried out at a synchrotron radiation facility showed that the distance between nanolayers was around 2.6 nm and TEM confirmed the fine sheet-like structure. The mechanism of the formation the nacre-like structure and its characterization were discussed.